Engineered Extracellular Vesicles From Human Periodontal-Ligament Stem Cells Increase VEGF/VEGFR2 Expression During Bone Regeneration - Pizzicannella, Jacopo; Gugliandolo, Agnese; Orsini, Tiziana; Fontana, Antonella; Ventrella, Alessia; Mazzon, Emanuela; Bramanti, Placido; Diomede, Francesca; Trubiani, Oriana (Frontiers in Physiology, 2019)
Bone regeneration represents still a challenge, in particular for calvarium defects. Recently, the development of biomaterials with the addiction of stem cells is giving promising results for the treatment of bone defects. In particular, it was demonstrated that scaffolds enriched with mesenchymal stem cells (MSCs) and/or their derivatives, such as conditioned medium (CM) and extracellular vesicles (EVs), may improve bone regeneration. Moreover, given the deep link between osteogenesis and angiogenesis, a successful approach must also take into consideration the development of vascularization. In this work we evaluated the bone regeneration capacity of a collagen membrane (3D-COL) enriched with human periodontal-ligament stem cells (hPDLSCs) and CM or EVs or EVs engineered with polyethylenimine (PEI-EVs) in rats subjected to a calvarial defect. We evaluated also their capacity to induce angiogenic factors. At first, in vitro results showed an increased expression of osteogenic markers in hPDLSCs cultured with the 3D-COL and PEI-EVs, associated also with the increased protein levels of Vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2). The increased expression of these proteins was confirmed also in vivo in rats implanted with the 3D-COL enriched with hPDLSCs and PEI-EVs. Moreover, histological examination evidenced in this group of rats the activation of bone regeneration and of the vascularization process. Also MicroCT imaging with morphometric analysis confirmed in rats transplanted with 3D-COL enriched with hPDLSCs and PEI-EVs an important regenerative process and a better integration level. All together, these results evidenced that the 3D-COL enriched with hPDLSCs and PEI-EVs may promote bone regeneration of calvaria defects, associated also with an increased vascularization.